A Tale of Two Fiscal Policies: Entrepreneurial and Entropic - Scott R. Sweetland (Educational Considerations, 2012)
Ohio’s school finance history can be characterized as progressive. Early state funding for school libraries was apportioned from state property tax receipts and distributed to local schools on a per-pupil basis. When equalization funding was invented to help poorer school systems, Ohio adopted that model of funding.
Keywords: Fiscal Policies; entrepreneurial; entropic; Ohio; economy; finance; funding; schools; program; voucher; community